Pengaruh Dosis Biofertilizer Formulasi Dan Biomass Azolla microphylla Terhadap Perubahan pH Air Pada Wadah Tanah Gambut - Zalukhu, Ida Yanti; Syafriadiman, Syafriadiman; Hasibuan, Saberina (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted on October 1th to December 31st, 2017 in the Kualu Nenas Village, Tambang District, Kampar regency, Riau Province. Objective of study was to determine the effect of doze of biofertilizer formulations, and biomass of Azolla microphylla, especially the change of pH in the each treatments. Method of this research used the experimental design by factorial experiment with Complit Randomized Block Design (CRBD). The fisrt treatment was used the doze of biofertilizer formulation (P), without doze of biofertilizer formulation (P0), doze 300 g/m2 (P1), doze 450 g/m2 (P2), doze 600 g/m2 (P3), doze 750 g/m2 (P4). And the second treatments was the biomass of Azolla microphylla (B), without biomass Azolla microphylla (B0), biomass Azolla microphylla 20 g/m2 (B1), biomass of Azolla microphylla 40 g/m2 (B2), biomass Azolla microphylla 60 g/m2 (B3). Result of this research showed the doze of biofertilizer formulation had in effects to the change of pH, while the biomass of Azolla microphylla not on the effect to the change of pH in the water. The best treatment for doze of biofertilizer formulation was P3 (doze 600 g/m2) was pH value 6,95±1,14. Then, the best of combination factors of using in the research was P3B3 (600 g/m2 and 60 g/m2), was pH value 7,17±1,10. Water quality parameters measuring were temperature, DO, and CO2 were good, and suppated to the cultivation in peatlands. Keywords: Biofertilizer Formulation, Biomass Azolla microphylla, pH, Peat Land